2000
DOI: 10.1081/pdt-100102043
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and In Vitro Evaluation of 1- and 4-Month Controlled Release Orntide PLA and PLGA Microspheres

Abstract: Orntide acetate was successfully incorporated into PLA and PLGA ms and the 1- and 4-month in vitro release profiles were achieved by polymer selection and optimization of the manufacturing parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Table 1 lists currently marketed formulations, indications for use, and duration of action. These depot formulations can deliver a sustained dose in vivo for varying periods of time, from weeks to months, [1][2][3][4][5][6] primarily owing to low degradation rates of the bulk eroding PLA and PLGA polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 lists currently marketed formulations, indications for use, and duration of action. These depot formulations can deliver a sustained dose in vivo for varying periods of time, from weeks to months, [1][2][3][4][5][6] primarily owing to low degradation rates of the bulk eroding PLA and PLGA polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of testosterone suppression for the 503 microspheres was expected because very little release from these microspheres was detected in vitro [26]. The initial suppression of testosterone in these two groups could be ascribed to the release of free Orntide adsorbed to the microspheres' surface or ascribed to stress during administration; stress also affected serum levels in the animals in the control group.…”
Section: Resultsmentioning
confidence: 97%
“…All microsphere batches resulted in significant decrease of testosterone levels compared with control groups. Statistically, the 503H (2) and 503H ( Cumulative Orntide AUCs were compared with in vitro release profiles previously obtained with a dialysis method [26]. Assuming that Orntide acetate has a very short biological half-life and that the peptide does not stimulate an antibody reaction, then the cumulative Orntide.AUC should reflect the in vivo release from sustained-release Orntide formulations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These formulations sustain drug levels in vivo for varying periods of time. 16 A previously published study showed that male rats treated with 120-day orntide microspheres were able to produce offspring upon cessation of treatment. 17 The goal of the present study was to assess the return to fertility in male rats, post treatment of a 1-year PLA microsphere dosage form of orntide, in comparison to untreated vehicle control and younger breeders.…”
Section: Introductionmentioning
confidence: 99%